Fundamentos biomecánicos en rehabilitación oral - Gerardo Becerra-S (Universidad de Antioquia, 2005)
The biological, mechanical and esthetic factors are the rational bases in the treatment for both the conventional prosthesis on natural teeth and for prosthesis on implants. The aim of this article is to review various biomechanical factors involved in both kinds of prosthesis. In reference to conventional prosthesis; retention and stability, abutment teeth valuation, anterior and canine teeth replacement, occlusal morphology and relationship between traumatic occlusion and cervical lesions, are considered. Among the biomechanical aspects in relation with prosthesis supported by oseointegrated implants, the following can be mentioned: biomechanics in natural and restored dentition, the combination of implant-natural tooth as abutments for a fixed partial prosthesis, the configuration of the arch and implants position, implants number, length and diameter of implants, implants in the molars area, passive adaptation and comparison between screwed and cemented